Spiritual Care for Nasopharyngeal Cancer Patients with Risk of Spiritual Distress: A Case Study - Pranatarini, Nur Azizah; Mulyono, Wastu Adi; Sumarwati, Made (Journal of Bionursing, 2025)
Background : Complications from cancer treatment therapy will cause physical and psychological problems for the rest of their lives. The physical and psychological problems experienced by cancer sufferers will rise spirituality within them. Spirituality sometimes becomes negative when an individual's spiritual needs are not facilitated properly or is called spiritual distress. Spiritual distress can be overcome through khusyuk in prayer therapy which can increase positive motivation and change behavior for the better. Purpose : This report aims to determine the effect of spiritual care of khusyuk prayer therapy on Nasopharyngeal Cancer patient with risk of spiritual distress to increase their ability to make sense of life and reduce feelings of guilt over their illness. Result : After doing the khusyuk prayer therapy intervention for 7 days, there was an increase in the patient's self-efficacy and quality of life. This shows that khusyuk prayer therapy can increase positive motivation in patients. Conclusion : Spiritual care with khusyuk prayer therapy can increase the motivation of nasopharyngeal cancer patients to make behavioral changes. Keyword : Khusyuk prayer, nasopharyngeal cancer, religious coping, self-efficacy, spiritual distress